METODE ROLE PLAY DAN MEDIA ANIMASI UNTUK MENINGKATKAN KETERAMPILAN BERBICARA BAHASA JEPANG DI SMA - Merry11, Ruli Hardi2, Suwaib Ami Lapasau (Faktor Jurnal Ilmiah Kependidikan, 2015)
Abstract: This research is aimed to acquire some knowledges of how to improve student’s tango (vocabulary) by using role play as a teaching method and animation  as media in teaching Japanese proficiency in SMAN I bilingual class XI  South Tangerang. This method is used in making some basic conversation such as greeting, introducing oneself and describing job. The results of the student’s evaluation before the research reached only an average of 62.5. As an effort to improve the student’s tango in Japanese language, it requires new innovations in teaching Japanese proficiency by using some  methods which have not been used before and media animation that can make learning more attractive than ever. The results of this study has showed some improvements in raising the quality of learning Japanese tango which is characterized by the acquisition of the average value of the two cycle oral test of 79.27. This means that it has exceeded the target achievement of competence of an indicator set by school of 90%.  Keywords: Tango., animation., role play method., Japanese proficiency